Analisis Faktor-Faktor yang Mempengaruhi Kualitas Pembiyaan Nasabah dalam Program Relaksasi Pandemi Covid-19 di PT Bank Sumut Syariah Kantor Cabang Pembantu H.M. Joni - Fitri Rahmadani Harahap; Nurul Jannah (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2022)
PT Bank Sumut utilizes the stimulus or relaxation from this regulator to help ease the burden on customers and at the same time mitigate potential credit risk. The extension of the restructuring policy is expected to help ease debtors in carrying out their obligations during the COVID-19 pandemic. This study aims to analyze what factors affect the quality of customer financing in the COVID-19 pandemic relaxation program at PT Bank Sumut Syariah KCP HM. Joni. The implementation of this restructuring also has an impact on the quality of financing productive assets, especially at KCP Syariah HM Joni. The Collectibility Ratio, NPF and Number of Non-Performing Customers have decreased (improved) since May 2020 both Collectibility 2 and Collectability 3,4, and 5. Several factors causing the decline in debtor collectibility of the Covid-19 Pandemic Relaxation Program are caused by several Economic Factors, Debtor Factors and Bank Internal Factors and other External Factors.